Oligodendroglial cell death in jimpy mice: an explanation for the myelin deficit - Knapp, PE (J Neurosci, 1986)
Neuroglial cell death was investigated in 3 white matter tracts of jimpy and normal mice. In normal animals, glial death during development ranged from 0.5 to 2.7% of the total glial population. The number of dying glial cells was significantly higher in jimpy animals at times corresponding with oligodendroglial proliferation and the onset of myelination in each tract. At certain ages, over 10% of the glial population were pyknotic at the light-microscopic level. Dying glial cells that were identified ultrastructurally presented the characteristics of oligodendrocytes. Premature death of oligodendrocytes presents a simple explanation for the gross deficits of myelin in jimpy animals. The shortened life span of the jimpy oligodendrocyte may preclude the elaboration of a normal myelin sheath. The jimpy model may prove to be a valuable tool in delineating a role for normal neuroglial cell death during the development of the nervous system.